Knowledge, attitude, and practice in treating pregnant women: A questionnaire survey among dental students of Mangalore city - Sherin James; Priyal Rohan (Journal of Indian Association of Public Health Dentistry, 2018)
Introduction: Good oral health is a key to overall health and wellbeing. It is essential and safe and can prevent long-term health issues. The role of oral health professionals includes providing preventive services and restorative treatment along with anticipatory guidance for pregnant women and their children. Aim: The objective of the study was to assess the knowledge, attitude, and practice among dental interns and final-year students in treating pregnant women. Materials and Methods: A questionnaire study was conducted in a private dental college in Mangalore city which included 140 students. A study-specific questionnaire was prepared to collect the data. Descriptive analysis was done. Statistical analysis was done with the help of the Statistical Package for Social Sciences version 17 (SPSS Inc., IBM, Chicago, IL, USA). Results: On average, there was enough knowledge among students regarding oral health. Nearly 39.3% of students had sufficient knowledge regarding management of pregnant women in a dental chair, and the students considered textbooks (49%) and lecture (25%) as their prime source of knowledge. About 39.3% of the clinical students educated the pregnant patients regarding their oral health and its influence on the fetus. About 42.1% educated occasionally and 18.6% never took pain to bring awareness among pregnant ladies. Regarding the antibiotic and analgesic of choice for pregnant women, very few had other options other than amoxicillin (77.1%) and paracetamol (73.6%). Single prescription over polypharmacy was supported by 77.7% students. Conclusion: The finding underscores the knowledge and information of dental students in the fundamentals of dental management of pregnant women to be satisfactory. Improvement is needed to increase the awareness of clinical students toward different types of critical treatment.